Emerging roles of calcium‐activated K channels and TRPV4 channels in lung oedema and pulmonary circulatory collapse. (16th September 2016) - Simonsen, U.; Wandall‐Frostholm, C.; Oliván‐Viguera, A.; Köhler, R.
Abstract: It has been suggested that the transient receptor potential cation (TRP) channel subfamily V (vanilloid) type 4 (TRPV4) and intermediate conductance calcium‐activated potassium (KCa3.1) channels contribute to endothelium‐dependent vasodilation. Here, we summarize very recent evidence for a synergistic interplay of TRPV4 and KCa3.1 channels in lung disease. Among the endothelial Ca 2+ ‐permeable TRPs, TRPV4 is best characterized and produces arterial dilation by stimulating Ca 2+ ‐dependent nitric oxide synthesis and endothelium‐dependent hyperpolarization. Besides these roles, some TRP channels control endothelial/epithelial barrier functions and vascular integrity, while KCa3.1 channels provide the driving force required for Cl − and water transport in some cells and most secretory epithelia. The three conditions, increased pulmonary venous pressure caused by left heart disease, high inflation pressure and chemically induced lung injury, may lead to activation of TRPV4 channels followed by Ca 2+ influx leading to activation of KCa3.1 channels in endothelial cells ultimately leading to acute lung injury. We find that a deficiency in KCa3.1 channels protects against TRPV4‐induced pulmonary arterial relaxation, fluid extravasation, haemorrhage, pulmonary circulatory collapse and cardiac arrest in vivo . These data identify KCa3.1 channels as crucial molecular components in downstream TRPV4 signal transduction and as a potential target for the prevention of undesired fluid extravasation, vasodilatation and pulmonary circulatory collapse.